2021
DOI: 10.1186/s12905-021-01353-x
|View full text |Cite
|
Sign up to set email alerts
|

Women in a situation of homelessness and violence: a single-case study using the photo-elicitation technique

Abstract: Background Violence against women places them in a vulnerable position with regard to homelessness. Although sometimes invisible, women’s homelessness is a complex reality shrouded in dramatic biographies that should be sensitively addressed to avoid revictimization. Methods With the aim of understanding the chaotic discourse of homeless women’s experiences of violence, a qualitative single-case study was conducted using the photo-elicitation techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Eight studies were conducted with participants from diverse ethnic origins or with an exclusively non-white sample of participants. The samples of participants included between 6 and 142 women, but two studies (i.e., Bjørnholt, 2019 ; Posada-Abadía et al, 2021 ) selected only one participant for the analysis (i.e., study case). Most of the studies ( n = 10) reported semi-structured interviews as data collection method.…”
Section: Methodsmentioning
confidence: 99%
“…Eight studies were conducted with participants from diverse ethnic origins or with an exclusively non-white sample of participants. The samples of participants included between 6 and 142 women, but two studies (i.e., Bjørnholt, 2019 ; Posada-Abadía et al, 2021 ) selected only one participant for the analysis (i.e., study case). Most of the studies ( n = 10) reported semi-structured interviews as data collection method.…”
Section: Methodsmentioning
confidence: 99%
“…The theory of ENP provides a critical framework for probing contextual and conceptual categories that may clarify the transformation process experienced by nurses engaged in social justice. Indeed, the theory of ENP has been cited in several topics, such as the future of nursing31 and nursing policy32 as well as studies exploring COVID-19 and racism33 and unhoused women experiencing violence 34. The theory of ENP has also influenced the creation of a middle-range theory in forensic nursing35 and in a concept analysis of nursing activism 36.…”
Section: Evaluation Of the Theory Of Enpmentioning
confidence: 99%
“…Indeed, the theory of ENP has been cited in several topics, such as the future of nursing 31 and nursing policy 32 as well as studies exploring COVID-19 and racism 33 and unhoused women experiencing violence. 34 The theory of ENP has also influenced the creation of a middle-range theory in forensic nursing 35 and in a concept analysis of nursing activism. 36 To date, there has only been one other analysis on the theory of ENP.…”
Section: Usefulnessmentioning
confidence: 99%
“…The basis to this is inclusion health [ 2 ], a research, service and policy agenda that seeks to promote health and target health inequities among marginalised communities [ 3 ]. Inclusion health is particularly salient for women experiencing homelessness due to their high rates of physical and mental health illnesses [ 4 7 ], exposure to violence, abuse, and addiction [ 4 , 6 , 8 10 ], and higher mortality rates than their male counterparts, or the general population [ 11 ]. Despite these multifaceted and complex healthcare needs, studies show that women experiencing homelessness are an underserved population across health and social care services [ 10 ].…”
Section: Introductionmentioning
confidence: 99%